IMPLEMENTASI PENDIDIKAN KARAKTER UNTUK MENANAMKAN NILAI PEDULI SOSIAL SESAMA BERDASARKAN HADITS DI RA AISYIYAH TANJUNGSARI - Nurul Riyatin; Nurmini Arsad; Nurlaela (CV Edujavare Publishing, 2025)
This research wasbased on the problem of how to instill social caring aharacters in schools and how teachers implement social values based on hadith. From the problems that arise, the aim is to familiarize students with implementing the value of social care in their living environment. This type of research uses descriptive qualitative, namely research that contains information about student character education in instilling social care based on hadiththe data sources in this research include primary data and secondary data. Primary data includes guru and students at RA Aisyiyah Tanjungsari. The result of the research carried out ae character education implemented by guru to instill a spirit of social care for others with the habit of praying. Then, implementing social care character education is by filling the donation can every day after the dhuha prayer. Student are instilled with the values of howimportant and beneficial giving is. Furthermore, in instilling the value of hadiths about Sedekah, the teacher provides routine habits for students recite hadithsincluding Sedekah hadiths every day accompanied by reciting short letters and daily prayers. Apart from that, the homeroom teacher and accompanying teachers always provide motivation to continue learning to become people who like to pray and continue to spread kindness to others.